Messiaen's musical techniques: The composer's view and beyond - Healey, Gareth (Surrey Ashgate Publishing, 2013)
Despite Messiaen's position as one of the greatest technical innovators of the twentieth century, his musical language has not been comprehensively defined and investigated. Given the reliance on idiosyncratic techniques, clear comprehension of the music is impossible without a detailed knowledge of Messiaen's methods. Gareth Healey charts their development and interconnections, considers their relationship with formal structures, and applies them in refined and extended form to works for which Messiaen himself left no published analysis.